Die Entwicklung des Sonderschulwesens in den westdeutschen Ländern Empfehlungen und Organisationsbedingungen - Dietze, Torsten (Perspektiven sonderpädagogischer Forschung, 2019)
In the school year 2017/18, about 317,000 students with ascertained "special educational needs" have been taught in "special schools" (german: "Sonderschule" or "Förderschule") in Germany. These special schools are still the place of study for about 6 of 10 of all students with special educational needs. Despite these high numbers of students, the actual organizational conditions at the special schools are hardly in the focus of special pedagogical research. The content of this thesis, therefore, is to elaborate on the development of the special education system with regard to its real organizational conditions in the light of national educational policy recommendations (Western Germany). On the one hand the database consists of publications by national actors in the school system, in particular the KMK (Standing Conference of the Ministers of Education and Cultural Affairs of the Länder) and the special education association VDS (today's name: Verband Sonderpädagogik e.V.), and on the other hand it consists of the official school statistics data of the Federal Statistical Office and the statistical offices of the Länder as well as the statistics on special education of the KMK. The educational policy recommendations are being compared to the real development. This is done for each defined individual main area of support. Thus, special-purpose research is added to the existing pedagogic research. The research is supplemented by further analyses, such as the proportion of boarding schools or the importance of private schools. Finally, extensions to the statistical database will be developed in order to more specifically illustrate the learning conditions at special schools. Further, reference is also made to statistical needs for the future mapping of the inclusive special educational support.